TRANSFORMASI AKHLAK NABI DALAM NOVEL AYAT-AYAT CINTA (The Transformation of the Prophet Morality in the Novel of Ayat-Ayat Cinta ) - Asep Supriadi; Mamad Ahmad (SAWERIGADING, 2017)
Religious literature is a literature containing religious values. One of them is the novel of Ayat-Ayat Cinta by Habiburrahman El-Shirazy. This research discusses the transformation of prophet morals in the novel of Ayat-ayat Cinta. The purpose of this study is to express the character of the prophet in the novel of Ayat-ayat Cinta. This research uses qualitative descriptive method with receptive and intertextual approaches. The findings obtained from the results of this study are (1) the wife must obey the husband and keep the honor, (2) respect the guests and tolerance, (3) respect to women, (4) looking for and praying for the sick people, 5) the procedure of associating with non-muhrim, (6) marriage and polygamy, (7) banned bribes, (8) must seek knowledge, (9) the importance of tahajud.AbstrakSastra keagamaan adalah sastra yang mengandung nilai-nilai ajaran agama. Salah satunya adalah novel Ayat-Ayat Cinta karya Habiburrahman El-Shirazy. Penelitian ini membahas transformasi akhlak nabi dalam novel Ayat-ayat Cinta. Tujuan penelitian ini adalah mengungkapkan akhlak nabi dalam novel Ayat-ayat Cinta. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan resepsi dan intertekstual. Berdasarkan hasil kajian, dalam novel Ayat-ayat terdapat akhlak nabi, anatara lain: (1) istri harus taat kepada suami dan menjaga kehormatan, (2) menghormati tamu dan sikap toleransi, (3) menghormati dan menghargai perempuan, (4) menengok dan mendoakan orang sakit, (5) tata cara bergaul dengan bukan muhrim, (6) pernikahan dan poligami, (7) dilarang suap-menyuap, (8) wajib mencari ilmu, (9) pentingnya melaksanakan salat tahajud.